The contribution of arterial blood gases in cerebral blood flow regulation and fuel utilization in man at high altitude - Willie, Christopher K (J Cereb Blood Flow Metab, 2015)
The effects of partial acclimatization to high altitude (HA; 5,050 m) on cerebral metabolism and cerebrovascular function have not been characterized. We hypothesized (1) increased cerebrovascular reactivity (CVR) at HA; and (2) that CO(2) would affect cerebral metabolism more than hypoxia. PaO(2) and PaCO(2) were manipulated at sea level (SL) to simulate HA exposure, and at HA, SL blood gases were simulated; CVR was assessed at both altitudes. Arterial–jugular venous differences were measured to calculate cerebral metabolic rates and cerebral blood flow (CBF). We observed that (1) partial acclimatization yields a steeper CO(2)-H(+) relation in both arterial and jugular venous blood; yet (2) CVR did not change, despite (3) mean arterial pressure (MAP)-CO(2) reactivity being doubled at HA, thus indicating effective cerebral autoregulation. (4) At SL hypoxia increased CBF, and restoration of oxygen at HA reduced CBF, but neither had any effect on cerebral metabolism. Acclimatization resets the cerebrovasculature to chronic hypocapnia.